Methylene blue removal by electrophoretic deposition coupled with MnO2/GO material - Hồ, Xuân Anh Vũ; Vũ, Thị Tường Vy; Nguyễn, Hải Phong (Hue University Journal of Science: Natural Science, 2022)
Graphene oxide (GO) was synthesized with the improved Hummer method and chemically modified with manganese dioxide (MnO2) to obtain an MnO2/GO composite. The properties of the composite material were evaluated via infrared spectroscopy, UV-Vis spectroscopy, scanning electron microscopy combined with energy-dispersive X-ray spectroscopy, and image mapping. The parameters studied in the method of electrophoretic deposition (EPD) are pH, electrolysis potential, electrolysis time, sodium chloride concentration, and the mass of the composite. Under suitable experimental conditions, the EPD method provides a rate of colour removal and chemical oxygen demand (COD) of methylene at 99.64 and 85.85%. This result shows the potential of the EPD method coupled with MnO2/GO composite to remove organic pigments in the aqueous medium.